Approximation of functions defined on the real axis by operators generated by λ-methods of summation of their Fourier integrals - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain asymptotic equalities for upper bounds of the deviations of operators generated by λ-methods (defined by a collection Λ=λσ(·) of functions continuous on [0; ∞) and depending on a real parameter σ) on classes of (ψ, β)-differentiable functions defined on the real axis.